Cobolt "bullets" for beef cattle - Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Earlier work at this station indicated that supplemental trace minerals may be of value in some instances. Introduction of the so-called cobalt “bullet” has made it possible to study one of these trace minerals alone as a dietary supplement.
Keywords: Cattle; Cobalt bullets; Carcass data